Unveiling herbicide tolerance in major oilseed crops: UNVEILING HERBICIDE TOLERANCE IN MAJOR OILSEED CROPS - P ASHOKKUMAR; A MAHALINGAM; N MANIVANNAN; G SENTHIL RAJA; P VEERAMANI (Journal of Oilseeds Research, 2024)
Herbicide tolerance in oilseed crops has revolutionized modern agriculture and offered effective weed management solutions while enhancing crop productivity. This comprehensive review explores various facets of herbicide tolerance, from its underlying mechanisms and historical evolution to its economic, environmental, and regulatory implications. We delve into the genetic basis of herbicide tolerance, elucidating the mechanisms that confer resistance in oilseed crops. The historical development of herbicide-tolerant varieties, from glyphosate-tolerant soybeans to novel traits in canola and sunflowers, reflects the evolving relationship between scientific innovation and industry dynamics. Economic analyses underscore the significant cost savings and yield improvements associated with herbicide tolerance while emphasizing the importance of sustainable weed management practices. Environmental considerations, including the impact on non-target organisms and biodiversity conservation, are evaluated alongside the regulatory frameworks governing the safe and responsible adoption of herbicide-tolerant varieties. Emerging trends in genetic engineering, biotechnology, and regulatory oversight offer promising avenues for future innovation and sustainability. To conclude, herbicide tolerance in oilseed crops represents a valuable tool for modern agriculture, contributing to global food security while necessitating careful stewardship and responsible management practices.